SEBUAH PENELITIAN MENGENAI KEMAMPUAN SISWA KELAS 2 MAN 1 PEKANBARU DALAM MEMAHAMI TEKS DESKRIPTIF - Rila Novita; Effendy Gultom; Afrianto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study is to find out the second year students’ ability of MAN 1 Pekanbaru in comprehending descriptive texts. The research data were collected in November 2016. The subject of this research was class XI MIA 5 which has 30 students. The data were collected using reading comprehension test with multiple choice type. The test contained 40 items. Based on the research, it was found out that the ability of the second year students in comprehending descriptive texts is in good level with the mean score of 72.33. The students’ mean score in finding main ideas is in good level with the mean score of 78.00. The students’ mean score in finding factual information is in good level with the mean score of 72.00. The students’ mean score in finding meaning of vocabulary is in good level with the mean score of 71.33. The students’ mean score in finding reference is in good level with the mean score of 64.67. The students’ mean score in finding inference is in good with the mean score of 68.67. The students’ mean score in identifying generic structure is in mediocre level with the mean score of 56.00. The students’ mean score in identifying language features is in good level with the mean score of 68.00. The students’ mean score in identifying social function is in good level with the mean score of 74.00. As a conclusion, the highest score obtained by the students is in finding main ideas with the mean score of 78.00 which is categorized into good level, and the lowest score that the students got is in identifying generic structure with the mean score of 56.00 which is categorized into mediocre level.